ASSESSMENT OF INSECURITY IN SENIOR SCHOOLS IN IBI LOCAL GOVERNMENT AREA, TARABA STATE, NIGERIA - Ifeoma Priscillilian Okafor; Isiaka Abdulaziz; Thompson Toryuha AUN (Sociology Education, Teaching Training and Education Faculty, Muhammadiyah University of Kupang, 2025)
One major problem affecting Nigeria today, which also bothers every dick, tom and harry is insecurity. Consequently, insecurity has taken various forms in different parts of the country, as there has been educational, social, and physical insecurity among residents in Ibi, Taraba. When a nation is saddled with the problem of insecurity every other plan is put on hold. The hope for the country seems to be grim if children cannot go to school. It is on this light that this researcher deems it fit to assess insecurity among senior schools in Ibi Local Government Area, Taraba State. Quantitative research of descriptive survey design was adopted in the study. The research covered all schools in Ibi LGA. The population for this study were all stakeholders (13 principals, 23 Vice principals, 38 HODs and 146 school prefects) in public senior schools in Ibi LGA were 64, and 20 schools as well as 220 participants were sampled. The researcher used Insecurity in Senior Schools Questionnaire (ISSQ) in eliciting information for this study. Percentage was used to describe the demographic characteristics of the respondents, while research questions and hypotheses were answered and tested using percentage, mean rating, t-test and ANOVA were adopted for hypothesis. The study discovered the level of insecurity in senior schools in Ibi Taraba was high; the three main causes of insecurity in senior secondary schools in Ibi Local Government Area, Taraba State were: bad governance mismanagement, lack of accountability and transparency; the three main solutions to insecurity in senior schools in Ibi, Taraba: having crisis response team development for emergencies; networking or holistic approach; and getting a secure school design. Among other things, stakeholders in education to ensure that the level of insecurity should be reduced to barest minimum.